Development of a Classical Conditioning Task for Humans Examining Phasic Heart Rate Responses to Signaled Appetitive Stimuli: A Pilot Study - Sayão, Alessandra; Alves, Heloisa; Furukawa, Emi; Schultz Wenk, Thomas; Cagy, Mauricio; Gutierrez-Arango, Samantha; Tripp, Gail; Caparelli-Dáquer, Egas (Frontiers in Behavioral Neuroscience, 2021)
Cardiac responses to appetitive stimuli have been studied as indices of motivational states and attentional processes, the former being associated with cardiac acceleration and latter deceleration. Very few studies have examined heart rate changes in appetitive classical conditioning in humans. The current study describes the development and pilot testing of a classical conditioning task to assess cardiac responses to appetitive stimuli and cues that reliably precede them. Data from eighteen adults were examined. They were shown initially neutral visual stimuli (putative CS) on a computer screen followed by pictures of high-caloric food (US). Phasic cardiac deceleration to food images was observed, consistent with an orienting response to motivationally significant stimuli. Similar responses were observed to non-appetitive stimuli when they were preceded by the cue associated with the food images, suggesting that attentional processes were engaged by conditioned stimuli. These autonomic changes provide significant information about classical conditioning effects in humans.